(untitled) (Élisée - Revista de Geografia da UEG, 2023)
The thought of Friedrich Ratzel and his methodological contributions to geography Abstract: This bibliographic review effort about the work of Friedrich Ratzel (1844-1904) puts us together with so many other efforts to (re)interpret his thinking. Even occupying a prominent place regarding the formulation of geographic science, many of his ideas and studies have been less or poorly used over the years due to misinterpretations. In this sense, our general objective is to reflect on the methodological contributions of Ratzel’s thinking to the construction of geographic science. We will also be looking at analyzing some of your core ideas by embodying some key concepts, the influences that led to the construction of his thought and how he had been used and interpreted over the years. Finally, we reinforce the importance of other efforts like this so that we can demystify some ideas and conclusions about Ratzel and his work. Keywords: methodological contributions, human geography, State, territory.